2021
DOI: 10.1039/d1cc00936b
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical SARS-CoV-2 biosensor inspired by glucose test strip manufacturing processes

Abstract: Vincent J Vezzaa, Adrian Butterwortha, Perrine Lasserrea, Ewen O Blaira, Alexander MacDonalda, Stuart Hannaha, Christopher Rinaldib, Paul A Hoskissonc, Andrew C Wardd, Alistair Longmuire, Steven Setforde, Eoghan CW Farmerf, Michael...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 18 publications
2
43
0
Order By: Relevance
“…This is attributable to the VPSS viral inactivation medium which contains a surfactant that modifies the electrochemical signal, leading to a non-specific reduction in impedance, contrasted to the non-sample reference measurement performed in SB buffer that affects both positive and negative samples. Furthermore, the drop in impedance seen for inactivated clinical samples is consistent with work previously published within the group using ACE2 modified gold surfaces 29 . Importantly, the results show that a significant degree of change in Rct occurs between the positive and negative samples (p< 0.01, two sample t-test) and that this separation follows the same trend as the laboratory-based study.…”
Section: Electrochemical Characterisation Of Thin-film Gold Electrodes (Tfge)supporting
confidence: 89%
See 2 more Smart Citations
“…This is attributable to the VPSS viral inactivation medium which contains a surfactant that modifies the electrochemical signal, leading to a non-specific reduction in impedance, contrasted to the non-sample reference measurement performed in SB buffer that affects both positive and negative samples. Furthermore, the drop in impedance seen for inactivated clinical samples is consistent with work previously published within the group using ACE2 modified gold surfaces 29 . Importantly, the results show that a significant degree of change in Rct occurs between the positive and negative samples (p< 0.01, two sample t-test) and that this separation follows the same trend as the laboratory-based study.…”
Section: Electrochemical Characterisation Of Thin-film Gold Electrodes (Tfge)supporting
confidence: 89%
“…SEP1 BIOTIP multichannel electrode printed circuit boards (PCB) (Bath, UK) were used for clinical sample testing and prepared according to the procedure described by Vezza et al (2021) 29 . Positive and negative SARS-CoV-2 samples in Viral PCR Sample Solution (VPSS) were obtained from NHS Glasgow Royal Infirmary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) . This value is lower than for the biosensors in the literature [ [12] , [13] , [14] , [15] , [16] , [17] ] [ [12] , [13] , [14] , [15] , [16] , [17] ] [ [12] , [13] , [14] , [15] , [16] , [17] ] and competitive with the device developed by Rahmadi et al [ 18 ], being also sufficient to detect SARS-CoV-2 virus in real samples, as demonstrated later on. where S blank is the signal of a control sample, and SD is the standard deviation.…”
Section: Resultsmentioning
confidence: 69%
“…For the presence of the spike proteins is a clear indicator of infection as is the case of the genetic material detected by genosensors or with RT-PCR. This has actually been exploited for SARS-CoV-2 [ [12] , [13] , [14] , [15] , [16] , [17] , [18] ].…”
Section: Introductionmentioning
confidence: 99%